External validation of a clinical risk score for the presence of cardiovascular autonomic neuropathy in type 1 diabetes - Pertile, Pietro; D'Ippolito, Ilenia; De Santis, Beatrice; Andreadi, Aikaterini; Lauro, Davide; Spallone, Vincenza (Journal of diabetes and its complications, 2025)
To validate in an independent external population a CAN Risk Score previously developed in type 1 diabetes (T1D) and validated for cardiovascular autonomic neuropathy (CAN) with a good diagnostic accuracy. Forty-seven participants with T1D (age 47.7 ± 13.2 years, duration of diabetes 30.0 (19.0–40.5) years, 24 males) underwent 4 cardiovascular reflex tests (CARTs) to diagnose early and confirmed CAN (according to 1 or 2 abnormal results). CAN Risk Score was calculated from resting heart rate, HbA1c, retinopathy and/or nephropathy, cardiovascular disease, HDL cholesterol, systolic blood pressure and smoking (range 0–10). Eleven participants (23.4 %) had CAN. The CAN Risk Score was higher in subjects with overall CAN (early and confirmed) (P = 0.0498) and with confirmed CAN (P = 0.0142) compared to those without, and correlated with CARTs severity (rho = 0.32, P = 0.026), Expiration/Inspiration ratio (r = −0.33, P = 0.0258) and Valsalva ratio (r = −0.47, P = 0.0015). A CAN Risk Score ≥ 4 was found in 19 participants and was associated with the presence of confirmed CAN (P = 0.0129). The CAN Risk Score showed an area under the ROC curve (AUC) of 0.802 ± 0.080 for confirmed CAN, and at the cut-off of 4, sensitivity, specificity and negative predictive values of 85.71 %, 67.50 % and 96.43 %. This study confirmed the diagnostic value of the CAN Risk Score and supports its inclusion in a diagnostic algorithm to identify candidates for CARTs, thereby reducing universal screening. Using routinely available clinical data as categorical variables, the score is easy to calculate and implement in clinical settings. •Despite its clinical impact, cardiovascular autonomic neuropathy (CAN) is often overlooked in screening and diagnosis.•We built a scoring system for CAN risk for type 1 diabetes using accessible clinical variables with good diagnostic accuracy.•In this study, we tried to validate this CAN Risk Score in an independent population and confirmed its diagnostic value.•The risk score can help select candidates for the cardiovascular autonomic tests, easing the burden of universal screening.